(untitled) (Research, Society and Development, 2019)
An asystematic review of the national and international literature was carried out, in order to reflect on the use and consequences of the use of the MMORPG. Theoretical material was used in the following electronic databases: Scielo, Google Scholar, Pepsic, Scopus, Sciense Direrct, books, theses and dissertations of CAPES, with the following descriptors "videogame", "MMORPG", "online gaming" gaming disorder "," internet "," behavioral addiction ", without delimitation of year of publication, in the English, Portuguese and Spanish languages, 75 articles were analyzed in two categories: General psychological effects and Gaming disorder. Results suggest that the MMORPG is a genre of game that produces positive and negative consequences, favoring the acquisition of new friendships, an increase in academic performance, as well as an increase in traits of hostility, aggressiveness, difficulty in solving problems, through a previous history of operation of personality. Also, the chronological time spent in the use of MMORPG appears as a crucial element for dependence, despite the other traits. It is suggested to conduct future empirical research involving Brazilian samples, since the studies in our country are incipient.